Molecular-Assisted Breeding of Cadmium Pollution-Safe Cultivars - Ni, Wen-Juan; Mubeen, Samavia; Leng, Xiao-Min; He, Chuntao; Yang, Zhongyi (Journal of agricultural and food chemistry, 2023)
Cadmium (Cd) contamination in edible agricultural products, especially in crops intended for consumption, has raised worldwide concerns regarding food safety. Breeding of Cd pollution-safe cultivars (Cd-PSCs) is an effective solution to preventing the entry of Cd into the food chain from contaminated agricultural soil. Molecular-assisted breeding methods, based on molecular mechanisms for cultivar-dependent Cd accumulation and bioinformatic tools, have been developed to accelerate and facilitate the breeding of Cd-PSCs. This review summarizes the recent progress in the research of the low Cd accumulation traits of Cd-PSCs in different crops. Furthermore, the application of molecular-assisted breeding methods, including transgenic approaches, genome editing, marker-assisted selection, whole genome-wide association analysis, and transcriptome, has been highlighted to outline the breeding of Cd-PSCs by identifying critical genes and molecular biomarkers. This review provides a comprehensive overview of the development of Cd-PSCs and the potential future for breeding Cd-PSC using modern molecular technologies.